Comparação entre os regimes transiente e permanente na obtenção de curvas de permeabilidade relativa - Viégas, Vitor Hartmann (2017)
Production of hydrocarbon reservoirs can be estimated using relative permeability curves obtained from laboratory tests on rock samples representative of the reservoir. These curves are among the parameters that most impact the results of reservoir simulations. In this work, two different methods were used to obtain these curves: unsteady state method on the relative permeability curves. In addition, different viscosity ratios were used in order to also verify the impact of the viscosity of the fluids on sensitivity of the relative permeability curves in relation to the evaluated methods. From the data of the displacement test on porous media the complete behavior of these curves was obtained. The points of the water permeability curves obtained by the steady state method presented lower values tha those obtained by the transient method. On the other hand , the oil permeability curves presented higher values. It was observed that the viscosity ratio employed in the tests has a great impact on the relative permeability curves, especially in the oil curve. In addition, it was observed that in more heterogeneous samples, the curves obtained by each flow regime have a great impact.